2013
DOI: 10.1136/annrheumdis-2012-202701
|View full text |Cite
|
Sign up to set email alerts
|

The autoantibody repertoire in periodontitis: a role in the induction of autoimmunity to citrullinated proteins in rheumatoid arthritis?

Abstract: We have shown that the antibody response in periodontitis is predominantly directed to the uncitrullinated peptides of the RA autoantigens examined in this study. We propose that this loss of tolerance could then lead to epitope spreading to citrullinated epitopes as the autoimmune response in periodontitis evolves into that of presymptomatic RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
93
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 52 publications
9
93
4
Order By: Relevance
“…Taken together, the results from our study, albeit with a limited number of positive samples, support the concept suggested by de Pablo et al ,1 and encourage further analyses.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Taken together, the results from our study, albeit with a limited number of positive samples, support the concept suggested by de Pablo et al ,1 and encourage further analyses.…”
supporting
confidence: 90%
“…We have read the article by de Pablo et al 1 with great interest. The authors reported higher frequencies of antibodies against the uncitrullinated form of fibrinogen and of the arginine containing α-enolase peptide-1 in patients with periodontitis compared with patients without periodontitis.…”
mentioning
confidence: 99%
“…As is the case with our cross-sectional findings, these data do not reflect antibody evolution in individual patients but show that antibodies against native peptides may occur prior to their anti-citrullinated peptide counterparts. Finally, an interesting study by de Pablo and colleagues showed that patients with periodontal disease, a possible trigger of RA, have a predominant antibody response against uncitrullinated peptides of RA autoantigens,36 suggesting that any evolution from periodontitis to pre-RA may start with a preselected antibody response against native antigens. This has been similarly suggested for patients with bronchiectasis,37 a population that may include individuals at risk to develop RA.…”
Section: Discussionmentioning
confidence: 99%
“…Although P. gingivalis is a promising candidate to explain the involvement of PD with ACPA production, there is not yet enough evidence to conclude that P. gingivalis in the PD-related bacterial flora is the cause of increasing positivity and level of ACPA. A recent study suggested that fine-specific ACPA detected in healthy subjects may not be specific to citrullinated peptide [23]. There is a possibility that non-specific oral inflammation by PD is important for ACPA production through undetermined processes.…”
Section: Discussionmentioning
confidence: 99%